A peptide derived from the core β-sheet region of TIRAP decoys TLR4 and reduces inflammatory and autoimmune symptoms in murine models - Achek, Asma; Kwon, Hyuk Kwon; Patra, Mahesh Chandra; Shah, Masaud; Hong, Riwon; Lee, Wang Hee; Baek, Wook Young; Choi, Yang Seon; Kim, Gi Young; Pham, Thuong L.H.; Suh, Chang Hee; Kim, Wook; et al. (EBioMedicine, 2020)
Background: TLRs are some of the actively pursued drug-targets in immune disorders. Owing to a recent surge in the cognizance of TLR structural biology and signalling pathways, numerous therapeutic modulators, ranging from low-molecular-weight organic compounds to polypeptides and nucleic acid agents have been developed. Methods: A penetratin-conjugated small peptide (TIP3), derived from the core β-sheet of TIRAP, was evaluated in vitro by monitoring the TLR-mediated cytokine induction and quantifying the protein expression using western blot. The therapeutic potential of TIP3 was further evaluated in TLR-dependent in vivo disease models. Findings: TIP3 blocks the TLR4-mediated cytokine production through both the MyD88- and TRIF-dependent pathways. A similar inhibitory-effect was exhibited for TLR3 but not on other TLRs. A profound therapeutic effect was observed in vivo, where TIP3 successfully alleviated the inflammatory response in mice model of collagen-induced arthritis and ameliorated the disease symptoms in psoriasis and SLE models. Interpretation: Our data suggest that TIP3 may be a potential lead candidate for the development of effective therapeutics against TLR-mediated autoimmune disorders. Funding: This work was supported by the National Research Foundation of Korea ( NRF-2019M3A9A8065098, 2019M3D1A1078940 and 2019R1A6A1A11051471). The funders did not have any role in the design of the present study, data collection, data analysis, interpretation, or the writing of the manuscript.
Keywords: Amino Acid Sequence; Animals; Anti-Inflammatory Agents; Autoimmunity; Cell Line; Cytokines; Disease Models, Animal; Immunologic Factors; Inflammation; Macrophages; Membrane Glycoproteins; Mice; Models, Molecular; Nitric Oxide; Peptides; Protein Conformation, beta-Strand; Psoriasis; Reactive Oxygen Species; Receptors, Interleukin-1; Signal Transduction; Structure-Activity Relationship; Toll-Like Receptor 4; Toll-Like Receptors; Antagonist; Collagen-induced arthritis; Decoy peptide; Psoriasis; Systemic lupus erythematosus; TLR4